Sifat Fisik dan Aktivitas Antioksidan Dendeng Daging Sapi dengan Penambahan Stroberi (Fragaria ananassa) sebagai Bahan Curing - Sunando, H.; Rahayu, S.; Baihaqi, M. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
Nitrate or nitrite that used on dendeng making as antioxidant agent and color stabilizer could forming toxic compound (nitrosamine). The Formation of nitrosamine could be inhibited by addition of natural antioxidant that contained in the fruits such as strawberry (Fragaria ananassa). The aim of this study was to evaluate the influence of stawberry as curing ingredient on physical properties and antioxidant activity of dendeng. Dendeng was made by addition of spices and combination of nitrite (0 ppm and 125 ppm) and strawberry (0%, 10%, 20%,30%) addition. Sample for analysis used fried dendeng. The result showed that pH value were affected by additon of nitrite and strawberry (P<0.01), but the objective color was affected by addition of nitrite only. Strawberry addition affected antioxidant activity of dendeng that was evaluated by scavenging activity on radical DPPH and antioxidant capacity (P<0.05). Interaction factor affected water activity and total phenolic content of dendeng (P<0.05). As conclusion strawberry addition up to 30% could be used as curing agent on dendeng making and increased antioxidant activity on dendeng product.